Odpowiedź :
Odpowiedź:
C.
Szczegółowe wyjaśnienie:
[tex]\left \{ {{{3x - 2y = - 18} \atop {-\frac{1}{2}} + 3y = 7 / * (-6)}} \right. [/tex]
[tex]\left \{ {{{3x - 2y = - 18} \atop {3x - 18y = - 42}} \right.[/tex]
[tex]\left \{ {{{|3x - 2y = - 18} \atop { - |3x - 18y = - 42}} \right.[/tex]
[tex]16y = 24[/tex]
[tex]y = 1 \frac{1}{2}[/tex]
Z tego punktu widzimy już że poprawna odpowiedź to C, ale obliczmy jeszcze [tex]x[/tex]
[tex]\left \{ {{3x - 2y = -18} \atop {y=1 \frac{1}{2}} \right.[/tex]
[tex]\left \{ {{3x - 3 = -18} \atop {y=1 \frac{1}{2}} \right.[/tex]
[tex]\left \{ {{3x = -15} \atop {y=1 \frac{1}{2}} \right.[/tex]
[tex]\left \{ {{x = -5} \atop {y=1 \frac{1}{2}} \right.[/tex]